Mathematical aspects of classical and celestial mechanics - Arnol'd, V. I. (Vladimir Igorevich), 1937-2010 (Encyclopaedia of mathematical sciences, 1997)
This book does not seek to serve as a textbook, nor to replace the original articles whose results it describes. The book's goal is to provide an overview, pointing out highlights and unsolved problems, and putting individual results into a coherent context. It is full of historical nuggets, many of them surprising. ... The examples are especially helpful; if a particular topic seems difficult, a later example frequently tames it. The writing is refreshingly direct, never degenerating into a vocabulary lesson for its own sake. The book accomplishes the goals it has set for itself. While it is not an introduction to the field, it is an excellent overview. ... " American Mathematical Monthly, Nov. 1989 "This is a book to curl up with in front of a fire on a cold winter's evening".